Economic Analysis of Existing Agroforestry Systems Among Different Categories of Farmers in Tehsil Bangana of Una District of Himachal Pradesh, India - Sharma, Som Dutt; Sharma, Jattin; Sharma, Kamal; Sharma, Dushyant (International Journal of Economic Plants, 2022)
The present study was conducted to evaluate the existing agroforestry systems and their economic returns in Tehsil Bangana of Una district of Himachal Pradesh, India during the year 2019−2020. A total number of 324 farmers were selected randomly from three categories viz., marginal, small, and medium based on landholding capacity for survey and data collection. The data was collected through a pre-tested schedule for personal interviews with the head of each household and field sampling. The study revealed that five agroforestry system types prevalent among different categories of farmers namely: AS, AH, AHS, HP, and SP. The bioeconomic of the different systems was analyzed by calculating the cost of cultivation, gross returns per hectare, net returns per hectare, and benefit: cost ratio. The higher net returns of agroforestry systems among different farmers categories were observed in AS, small farmer’s category (` 1,51761), and lowest were observed in SP, marginal farmer’s category (` 5,999). Benefit: cost ratio of agroforestry systems among different farmers category was observed maximum in AH, medium farmer’s category (1.89) whereas, minimum benefit: cost ratio was recorded in SP, marginal farmer’s category (1.72). Irrespective of farmers category, maximum mean benefit: cost ratio (1.88) was recorded in AHS and minimum (1.72) was observed in the SP system. Hence the study represents the clear picture of economic analysis of existing agroforestry systems which will help the local peoples to fulfill their basic needs and the researchers to gain the benefit from the agroforestry.